2007
DOI: 10.1002/hep.21802
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-κB and the hepatic inflammation-fibrosis-cancer axis

Abstract: Nuclear factor-B (NF-B) is a transcriptional regulator of genes involved in immunity, inflammatory response, cell fate, and function. Recent attention has focused on the pathophysiological role of NF-B in the diseased liver. In vivo studies using rodent models of liver disease and cell-targeted perturbation of NF-B activity have revealed complex and multicellular functions in hepatic inflammation, fibrosis, and the development of hepatocellular carcinoma-a process we have termed the "inflammation-fibrosis-canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
270
0
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 373 publications
(285 citation statements)
references
References 50 publications
11
270
0
3
Order By: Relevance
“…It has been reported that NF-κB activation is essential for inflammation and inflammation-associated cancerous changes [30]. Although NF-κB binds to a region of the COX-2 promoter known to be critical for COX-2 transcriptional activation in a number of other cell types [31,32], it is reported that NF-κB activation is not necessary for the induction of COX-2 by HBx [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NF-κB activation is essential for inflammation and inflammation-associated cancerous changes [30]. Although NF-κB binds to a region of the COX-2 promoter known to be critical for COX-2 transcriptional activation in a number of other cell types [31,32], it is reported that NF-κB activation is not necessary for the induction of COX-2 by HBx [17].…”
Section: Discussionmentioning
confidence: 99%
“…Unresolved inflammation induced-liver fbrosis leading to cirrhosis without effective control is the main risk factor for the development of HCC, termed inflammation-fibrosis-carcer axis (Elsharkawy and Mann, 2007). Recent study described that cytokines lymphotoxin a and ß and their receptor (LTbR) are upregulated in HBV-or HCVinduced hepatitis and HCC, indicating the role of sustained lymphotoxin signaling in hepatitis-induced HCC (Haybaeck et al, 2009).…”
Section: Role Of Hsc In Hcc Developmentmentioning
confidence: 99%
“…Recent study described that cytokines lymphotoxin a and ß and their receptor (LTbR) are upregulated in HBV-or HCVinduced hepatitis and HCC, indicating the role of sustained lymphotoxin signaling in hepatitis-induced HCC (Haybaeck et al, 2009). The transcriptional regulator nuclear factor-jB can act as a potential master orchestrator of the axis (Elsharkawy and Mann, 2007). In a diethylnitrosamine-induced hepatocarcinogenesis rat model, activated HSC were prominent in fibrous septa around and within dysplastic and carcinomatous nodules (Johnson et al, 1998).…”
Section: Role Of Hsc In Hcc Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…About 90% of HCC in patients is accompanied by hepatic cirrhosis, which results from the development of liver fibrosis (Yang and Roberts, 2010). Viral hepatitis infection leading to chronic inflammation apparently promotes fibrosis and hepatic carcinogenesis, known as the inflammation-fibrosis-cancer axis (Elsharkawy and Mann, 2007).…”
Section: Introductionmentioning
confidence: 99%